Clinical characteristics and predictors of 5-year survival among colorectal cancer patients in a tertiary hospital in Malaysia - Lim, Kean Ghee; Lee, Chit Seng; Hong, Daniel Jeng Chin; Ooi, Yong Song; Veettil, Sajesh K.; Ching, Siew Mooi; Burud, Ismail Abdul Sattar; Zakaria, Jasiah (AME Publishing Company, 2020)
Background: Colorectal cancer is the second most common cancer in Malaysia. Its disease burden is likely to increase over time owing to its current trends in this region. This study was undertaken to determine the 5-year survival rate and prognostic factors for survival in colorectal cancer patients treated in a tertiary hospital, in Malaysia. Methods: We reviewed the records of colorectal cancer patients treated in Hospital Tuanku Ja’afar Seremban, Malaysia from 2008 to 2012. Survival analysis at five years was performed using the Kaplan-Meier method. Cox proportional hazard regression analysis was carried out to determine the predictors of 5-year colorectal cancer survival. Results: Of the 275 patients, 43.3% were colon cancers, 51.8% were rectal cancers. Only 2.2% were diagnosed in Stage I. 28.7%, 33.1%, and 16.7% were in Stage II, III and IV respectively; 62/79 (78%) of Stage II patients were in Stage IIb; 15.7% of patients were below the age of 50 and fewer of them presented early (P=0.002). The overall 5-year survival was 46.5%. It was 67.9%, 50.5% and 12.8% for Stage I&II, III and IV patients respectively. Early stage of cancer (P<0.001) and age below the mean (P=0.01) were the most significant factor in predicting better survival. Gender and ethnic group were not associated with late presentation nor survival. Neither was there a difference between colon and rectum cancers nor patients who received elective surgical treatment compared to patients receiving other treatment first (P=0.085). Conclusions: Late presentation is the most important predictor for poor outcome for colorectal cancer in Seremban. Patients under the age of 50 years present late more often, but do not have poorer survival.